Motivated political reasoning: The formation of belief-value constellations - Kai Barron; Anna Becker; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
We study the causal relationship between moral values ("ought" statements) and factual beliefs ("is" statements) and show that, contrary to predictions of orthodox Bayesian models, values exert an influence on beliefs. This effect is mediated by prior political leanings and, thus, contributes to increasing polarization in beliefs about facts. We study this process of motivated political reasoning in a preregistered online experiment with a nationally representative sample of 1,500 individuals in the US. Additionally, we show that subjects do not distort their beliefs in response to financial incentives to do so, suggesting that deep values exert a stronger motivational force.
Keywords: C90; D72; D74; D83; P16; 330; Motivated Beliefs; Values; Polarization; Experiment